A control hardware based on a field programmable gate array for experiments in atomic physics - Bertoldi, A; C -H Feng; Imaz, H Eneriz; Carey, M; Naik, D S; Junca, J; Zou, X; Sabulsky, D O; Canuel, B; Bouyer, P; Prevedelli, M (arXiv.org, 2020)
Experiments in Atomic, Molecular, and Optical (AMO) physics require precise and accurate control of digital, analog, and radio frequency (RF) signals. We present a control hardware based on a field programmable gate array (FPGA) core which drives various modules via a simple interface bus. The system supports an operating frequency of 10 MHz and a memory depth of 8 M (2\(^{23}\)) instructions, both easily scalable. Successive experimental sequences can be stacked with no dead time and synchronized with external events at any instructions. Two or more units can be cascaded and synchronized to a common clock, a feature useful to operate large experimental setups in a modular way.